2020
DOI: 10.3390/electronics9030426
|View full text |Cite
|
Sign up to set email alerts
|

Research on Anti-Radiation Noise Interference of High Definition Multimedia Interface Circuit Layout of a Laptop

Abstract: In this paper, several aspects were studied, including the effect of an electromagnetic interference (EMI) noise interference strategy with High Definition Multimedia Interface (HDMI) 1.4, the analysis of a test on a printed circuit board (PCB) layout, and a comparison of the near field intensity radiation distribution between an EMI with a modified HDMI layout and an original layout. In this study, the near field detection instrument of APREL EM-ISight was employed to analyze the distribution of the strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Chien et al reported "Research on Anti-Radiation Noise Interference of High Definition Multimedia Interface Circuit Layout of a Laptop" [3]. In this paper, several aspects were studied, including the effect of an electromagnetic interference (EMI) noise interference strategy with High Definition Multimedia Interface (HDMI) 1.4, the analysis of a test on a printed circuit board (PCB) layout, and a comparison of the near field intensity radiation distribution between an EMI with a modified HDMI layout and an original layout.…”
Section: The Topics Of Intelligent Electronic Device and Its Applicatmentioning
confidence: 99%
“…Chien et al reported "Research on Anti-Radiation Noise Interference of High Definition Multimedia Interface Circuit Layout of a Laptop" [3]. In this paper, several aspects were studied, including the effect of an electromagnetic interference (EMI) noise interference strategy with High Definition Multimedia Interface (HDMI) 1.4, the analysis of a test on a printed circuit board (PCB) layout, and a comparison of the near field intensity radiation distribution between an EMI with a modified HDMI layout and an original layout.…”
Section: The Topics Of Intelligent Electronic Device and Its Applicatmentioning
confidence: 99%
“…However, as switching frequencies increase, the sizes of EMI filters also increase significantly, which is highly detrimental to improving converter power density. Additionally, hardware-based strategies such as soft-switching techniques [18] and optimized circuit layouts [19] are used for EMI suppression. However, soft-switching techniques require additional components, hindering cost reduction and the increase in power density.…”
Section: Introductionmentioning
confidence: 99%